2009
DOI: 10.1136/jnnp.2008.148122
|View full text |Cite
|
Sign up to set email alerts
|

Integrated care improves risk-factor modification after stroke: initial results of the Integrated Care for the Reduction of Secondary Stroke model

Abstract: Objective: Despite evidence demonstrating that riskfactor management is effective in reducing recurrent cerebrovascular disease, there are very few structured care programmes for stroke survivors. The aim was to implement and evaluate an integrated care programme in stroke. Methods: 186 patients with stroke were randomised to either the treatment (integrated care) or control (usual care) group and were followed up over 12 months. The Integrated Care for the Reduction of Secondary Stroke (ICARUSS) model of inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
129
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(135 citation statements)
references
References 30 publications
4
129
2
Order By: Relevance
“…19 -22 The components of these interventions included: assessment and review by an interdisciplinary stroke team plus personalized self-management plans 19 ; shared medical records; inpatient teaching about stroke plus provision of information leaflets 21 ; monthly risk factor reviews with a specialist stroke nurse; delivery of individualized secondary prevention advice plus use of patient-held records 22 ; and an integrated system of management. 20 The integrated system had multiple components, including using flowcharts to guide in-hospital and primary care prescribing; delivery of patient education on risk factor management by a nurse coordinator; prearranged follow-up appointments with a general practitioner (GP) at 2 weeks and 3, 6, 9, and 12 months postdischarge; telephone tracking of patients before the appointments to identify risk factor management problems; screening for depressive symptoms and provision of feedback to GPs; nurse coordinator monitoring; and intervention for suboptimal GP prescribing. 20 Only the integrated management trial demonstrated improved effects on risk factor management outcomes, but analysis was not by intention to treat and clustering was not taken into account.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…19 -22 The components of these interventions included: assessment and review by an interdisciplinary stroke team plus personalized self-management plans 19 ; shared medical records; inpatient teaching about stroke plus provision of information leaflets 21 ; monthly risk factor reviews with a specialist stroke nurse; delivery of individualized secondary prevention advice plus use of patient-held records 22 ; and an integrated system of management. 20 The integrated system had multiple components, including using flowcharts to guide in-hospital and primary care prescribing; delivery of patient education on risk factor management by a nurse coordinator; prearranged follow-up appointments with a general practitioner (GP) at 2 weeks and 3, 6, 9, and 12 months postdischarge; telephone tracking of patients before the appointments to identify risk factor management problems; screening for depressive symptoms and provision of feedback to GPs; nurse coordinator monitoring; and intervention for suboptimal GP prescribing. 20 Only the integrated management trial demonstrated improved effects on risk factor management outcomes, but analysis was not by intention to treat and clustering was not taken into account.…”
mentioning
confidence: 99%
“…20 The integrated system had multiple components, including using flowcharts to guide in-hospital and primary care prescribing; delivery of patient education on risk factor management by a nurse coordinator; prearranged follow-up appointments with a general practitioner (GP) at 2 weeks and 3, 6, 9, and 12 months postdischarge; telephone tracking of patients before the appointments to identify risk factor management problems; screening for depressive symptoms and provision of feedback to GPs; nurse coordinator monitoring; and intervention for suboptimal GP prescribing. 20 Only the integrated management trial demonstrated improved effects on risk factor management outcomes, but analysis was not by intention to treat and clustering was not taken into account. 20 Following the Medical Research Council Framework for the development and evaluation of complex health service interventions, 23 we conducted multiple studies over 5 years to inform the development of a novel intervention to improve stroke secondary prevention management.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Individuals can reduce their risk of secondary stroke by addressing the modifi able stroke risk factors through altering their lifestyle behaviors. 4,5 However, poststroke management of risk factors is typically suboptimal. [6][7][8][9] Information about secondary stroke prevention information is an important, but frequently neglected, part of the stroke information that should be routinely provided to patients and carers after stroke.…”
Section: Purposementioning
confidence: 99%
“…A multicenter trial in Australia developed a standardized integrated care (IC) model for patients after a stroke. 25 This IC model targeted seven modifiable risk factors including blood pressure, cholesterol, atrial fibrillation, body mass index (BMI), smoking, alcohol intake, and physical activity. The IC model included optimization of pharmacotherapy and patient education, with counseling specific towards stroke risk factor modification.…”
Section: Standardized Discharge Ordersmentioning
confidence: 99%